Online Experimentation @ REV2012 - Restivo, Maria Teresa; Cardoso, Alberto (International Journal of Online and Biomedical Engineering (iJOE), 2013)
In conferences, a participant is supposed to present his/her work to the audience in around 15-20 minutes.When the topics are in the experimental field multimedia components like pictures, video clips or animations are recommended to give to the experimental issues as much realism as possible.In topics like online engineering it is mandatory to have real resource demonstrations.A new model for specific conferences like those on online engineering topics, has been implemented. Participants are invited to get together and try to demonstrate their online resources.